Effects of insulin and leptin on human spermatozoa function and their cross-talk with nitric oxide and cytokines - Lampiao, Fanuel (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2009.